The Ideological Study of Judicials From The Formal Centralistis to The Legal Pluralism (Analysis of the Meaning of Judge on Article 5 paragraph (1) of Law Number 48 Year 2009 on Judicial Power) - Rina Yulianti; Mufarrijul Ikhwan (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2017)
Article 5 (1) of Law Number 48 Year 2009 concerning Judicial Power becomes ineffective if acentralistic ideology still working in view of the judge. The type of study used in this researchwas a non-doctrinal legal studies (sociolegal research). Research conducted in the DistrictCourt and Religious Court in Madura based on the judges perception by meaning of article 5paragraph (1) law 48/2009 and justices consideration to verdict making process. The resultsshowing the judges majority interpret the Article 5, paragraph 1 Law 28/2009 to legaldiscovery (rechtsvinding) as an efforts if a legal vacuum, otherwise the judges did notinterpret used living law when there are legal gaps. Thus showing domination of the state lawover the law that lives in society. DOI: 10.15408/jch.v5i2.4190